RSL Class II Transcription Factors Guide the Nuclear Localization of RHL1 to Regulate Root Hair Development. Issue 2 (13th December 2018) - Moon, Sunok; Cho, Lae-Hyeon; Kim, Yu-Jin; Gho, Yun-Shil; Jeong, Ho Young; Hong, Woo-Jong; Lee, Chanhui; Park, Hyon; Jwa, Nam‐Soo; Dangol, Sarmina; Chen, Yafei; Park, Hayeong; et al.
Abstract : Root Hair Defective Six Like (RSL) Class II family proteins regulate root hair development by mediating RHL1 import into the nucleus. Abstract: Root hairs are important for absorption of nutrients and water from the rhizosphere. The Root Hair Defective-Six Like (RSL) Class II family of transcription factors is expressed preferentially in root hairs and has a conserved role in root hair development in land plants. We functionally characterized the seven members of the RSL Class II subfamily in the rice ( Oryza sativa ) genome. In root hairs, six of these genes were preferentially expressed and four were strongly expressed. Phenotypic analysis of each mutant revealed that Os07g39940 plays a major role in root hair formation, based on observations of a short root hair phenotype in those mutants. Overexpression (OX) for each of four family members in rice resulted in an increase in the density and length of root hairs. These four members contain a transcription activation domain and are targeted to the nucleus. They interact with rice Root Hairless1 (OsRHL1), a key regulator of root hair development. When heterologously expressed in epidermal cells of Nicotiana benthamiana leaves, OsRHL1 was predominantly localized to the cytoplasm. When coexpressed with each of the four RSL Class II members, however, OsRLH1 was translocated to the nucleus. Transcriptome analysis using Os07g39940- OX plants revealed that 86 genes, including Class III peroxidases, were highly up-regulated. Furthermore, reactive oxygen species levels in the root hairs were increased in Os07g39940- OX plants but were drastically reduced in the os07g39940 and rhl1 mutants. Our results demonstrate that RSL Class II members function as essential regulators of root hair development in rice.